USE OF OSTEOTOMY IN POST-TRAUMATIC DEFORMITY OF FRONTAL SINUS ANTERIOR WALL. CASE REPORT - Němec, I (Acta chirurgiae plasticae, 2016)
Post-traumatic deformity of frontal sinus anterior table can be treated in various ways. Usage of a certain type of an implant is a common method. We performed an osteotomy and subsequent reduction of the fragments to reconstruct their anatomical position. Titanium miniplates and screws were used for fixation. This case report suggests a possible use of this method in patients with more extensive frontal sinus and distinct post-traumatic deformity. No similar case manages as described in our case report was found in the literature.
Keywords: Frontal Bone; čelní kost; dospělí; post-traumatic deformity cranial osteotomy.; fraktury lebky; Osteotomy; lidé; mužské pohlaví; osteotomie; Skull Fractures; Male; fracture; Frontal sinus; Frontal Sinus; sinus frontalis; Adult; Humans